Role of the carboxy groups of triterpenoids in their inhibition of the nucleation of amyloid β42 required for forming toxic oligomers. Issue 49 (31st May 2018) - Murakami, Kazuma; Yoshioka, Takuya; Horii, Shiori; Hanaki, Mizuho; Midorikawa, Satohiro; Taniwaki, Shinji; Gunji, Hiroki; Akagi, Ken-ichi; Kawase, Taiji; Hirose, Kenji; Irie, Kazuhiro
Abstract : The carboxy group of ursane-type triterpenoids plays a critical role in the suppression of toxic Aβ42 nucleation by targeting the monomer to trimer. Abstract : Herein we report that a preferable inhibition of the nucleation phase of Aβ42, related to the formation of toxic oligomers, by triterpenoids from medicinal herbs originates from a salt bridge of their carboxy groups with Lys16 and 28 in Aβ42. Such a direct interaction targeting the monomer, dimer, and trimer suppressed further oligomerization. In contrast, the corresponding congeners without carboxy groups failed to do so.